Vascular depression consensus report – a critical update. Issue 1 (December 2016) - Aizenstein, Howard; Baskys, Andrius; Boldrini, Maura; Butters, Meryl; Diniz, Breno; Jaiswal, Manoj; Jellinger, Kurt; Kruglov, Lev; Meshandin, Ivan; Mijajlovic, Milija; Niklewski, Guenter; Pospos, Sarah; et al.
Abstract Background Vascular depression is regarded as a subtype of late-life depression characterized by a distinct clinical presentation and an association with cerebrovascular damage. Although the term is commonly used in research settings, widely accepted diagnostic criteria are lacking and vascular depression is absent from formal psychiatric manuals such as the Diagnostic and Statistical Manual of Mental Disorders, 5th edition – a fact that limits its use in clinical settings. Magnetic resonance imaging (MRI) techniques, showing a variety of cerebrovascular lesions, including extensive white matter hyperintensities, subcortical microvascular lesions, lacunes, and microinfarcts, in patients with late life depression, led to the introduction of the term "MRI-defined vascular depression". Discussion This diagnosis, based on clinical and MRI findings, suggests that vascular lesions lead to depression by disruption of frontal–subcortical–limbic networks involved in mood regulation. However, despite multiple MRI approaches to shed light on the spatiotemporal structural changes associated with late life depression, the causal relationship between brain changes, related lesions, and late life depression remains controversial. While postmortem studies of elderly persons who died from suicide revealed lacunes, small vessel, and Alzheimer-related pathologies, recent autopsy data challenged the role of these lesions in the pathogenesis of vascular depression. Current data propose that the vascular depression connotation should be reserved for depressed older patients with vascular pathology and evident cerebral involvement. Based on current knowledge, the correlations between intra vitam neuroimaging findings and their postmortem validity as well as the role of peripheral markers of vascular disease in late life depression are discussed. Conclusion The multifold pathogenesis of vascular depression as a possible subtype of late life depression needs further elucidation. There is a need for correlative clinical, intra vitam structural and functional MRI as well as postmortem MRI and neuropathological studies in order to confirm the relationship between clinical symptomatology and changes in specific brain regions related to depression. To elucidate the causal relationship between regional vascular brain changes and vascular depression, animal models could be helpful. Current treatment options include a combination of vasoactive drugs and antidepressants, but the outcomes are still unsatisfying.